Analysis of Patient Safety Culture on Incident Reporting Compliance at Clinic X in the Bekasi Area - Gherriandi Raja Buana; Hana Badiiah; Thalia Carissa Maharani; Innocentius Bernarto (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Patient safety is an essential indicator in improving the quality of healthcare services. Patient safety culture plays a significant role in encouraging healthcare workers to report incidents as part of organizational learning. However, incident reporting in primary healthcare settings remains suboptimal. This study aimed to analyze the influence of patient safety culture on incident reporting compliance at Clinic X in Bekasi. This research used a quantitative approach with a cross-sectional design involving 35 subjects. Data were collected using the HSOPSC questionnaire and analyzed using descriptive statistics, Spearman correlation, and regression analysis. The results showed that patient safety culture was in the moderate category with a positive response rate of 65%–74%. The correlation test indicated a positive and significant relationship between patient safety culture and incident reporting compliance (p < 0.05). Regression analysis also demonstrated a significant effect of patient safety culture on reporting compliance. Teamwork, communication, and management support were identified as strengths, while non-punitive response to error, staffing, and overall patient safety perception required improvement. In conclusion, patient safety culture played a crucial role in improving incident reporting compliance. Strengthening a non-punitive culture, workload management, and optimizing reporting systems are necessary to enhance patient safety in primary healthcare settings.